2011
DOI: 10.3121/cmr.2011.964
|View full text |Cite
|
Sign up to set email alerts
|

Coalition Building and the Intervention Wheel to Address Breast Cancer Screening in Hmong Women

Abstract: Br east cancer is the most frequently diagnosed cancer among women in the United States, where 1 in 8 women will face breast cancer in their lifetime.1 In 2010, this translates to approximately 207,090 women who will be diagnosed with this disease, and about 54,010 who will die of breast cancer. 1While Caucasian women have the highest incidence of breast cancer in comparison to any other cultural group, Asian American and Pacific Islander (AAPI) women, in aggregate, are more likely to die from breast cancer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recently, increasing evidence demonstrated that miRNAs play an extensive and important role in the physiological processes of the body [35]. In addition, in developed countries such as the United States and throughout Europe, cancer is the second leading cause of human death, while it ranks second or third in developing countries [36]. Therefore, in order to further evaluate the accuracy of WINMDA in predicting potential disease–miRNA associations, we chose three kinds of cancers, i.e., colon neoplasms, gastric neoplasms, and prostate neoplasms, as case studies for WINMDA, and the prediction results were verified by recently published experimental studies and two databases, namely miR2Disease and dbDEMC.…”
Section: Results and Case Studiesmentioning
confidence: 99%
“…Recently, increasing evidence demonstrated that miRNAs play an extensive and important role in the physiological processes of the body [35]. In addition, in developed countries such as the United States and throughout Europe, cancer is the second leading cause of human death, while it ranks second or third in developing countries [36]. Therefore, in order to further evaluate the accuracy of WINMDA in predicting potential disease–miRNA associations, we chose three kinds of cancers, i.e., colon neoplasms, gastric neoplasms, and prostate neoplasms, as case studies for WINMDA, and the prediction results were verified by recently published experimental studies and two databases, namely miR2Disease and dbDEMC.…”
Section: Results and Case Studiesmentioning
confidence: 99%
“…In a systematic review, the PHI Model was used to analyze nurse‐led interventions that promoted the quality of life for older adults in 13 countries (Schaffer et al., 2017). Also, several authors have expanded on specific Wheel interventions in practice, including coalition‐building and outreach (Depki & Onitilo, 2011; Tembreull & Schaffer, 2006).…”
Section: Dissemination Of the Phi Wheelmentioning
confidence: 99%
“…IW has been started to be also used in studies and researches. In their study Depke and Onitilo (2011) specified that coalition-building among the IW's 17 interventions is important in terms of reducing obstacles and empowering trainings for raising awareness through the development of breast cancer screening programs among the women living in Hmong in Southeast Asia and creating health trainings (15). "Public Health Nursing Competences Tool/Criteria" has been developed in line with IW for the populationbased public health nursing.…”
Section: Intervention Wheel's Places Of Use and Examplesmentioning
confidence: 99%